Proliferative Vasculopathy Associated With Antiphospholipid Antibodies in Patients With Neurological Symptoms - Yeo, Jina; Hwang, Inpyeong; Sohn, Chul-Ho; Lee, Eunyoung Emily; Lee, Soon-Tae; Lee, Eun Bong; Park, Jin Kyun (Frontiers in Medicine, 2022)
Background: Proliferative vasculopathy (PV) associated antiphospholipid syndrome (APS) in the central nervous system is a rare un(der)recognized form of extra-criteria manifestations of APS. This study investigated the angiographic characteristics of carotid and cerebral arteries in patients with PV associated with antiphospholipid antibodies (aPLs). Methods: Patients with aPLs, neurologic symptoms and diffuse luminal narrowing on brain or carotid magnetic resonance angiography (MRA) were selected from electronic medical records. Vascular wall and intraluminal pathology were examined by high-resolution vessel wall MR imaging (VW-MRI). Results: Six men and five women who had diffuse luminal narrowing affecting the carotid and cerebral arteries were included. Median (interquartile range) anticardiolipin antibodies titer was 59.6 (28.3-134.0) units and anti-beta 2 glycoprotein I antibodies titer was 227.2 (59.0-1012.1) units. All patients had diffuse luminal narrowing in the carotid basilar and/or cerebral arteries, five in the internal carotid artery (ICA); two each in the middle cerebral artery (MCA) and vertebral artery; and one each in the basilar artery (BA) and posterior cerebral artery. On VW-MRI, four patients showed concentric thickening of the vascular walls of the ICA and/or MCA and two showed mild eccentric wall thickening of the ICA or BA. All patients received antithrombotic treatment. Diffuse narrowing did not improve on follow-up imaging. Conclusions: This study suggests that PV-aPL might be a distinct extra-criteria manifestation of APS that can manifest as long-segmental diffuse stenosis of carotid and cerebral arteries. It should be considered in relatively young patients with neurologic symptoms and aPLs.